Culture as a paradigm of regeneration in shrinking cities: Readings from the Oscar Niemeyer International Cultural Center in Avilés (Spain) - Mañá, Fernando Falomir; Salcedo, Rosio Fernández Baca (National Journal of City Management, 2020)
The Oscar Niemeyer International Cultural Center (2008-2011), a work signed by the Brazilian master of architecture in his last creation period, is the symbol chosen for the regeneration of Avilés (Spain), a shrinking city associated from the fifties of the last century to an industrialization model now in decline. To understand the relations established between the architectural work and the medieval city of Avilés, we will use the dialogical method based on the theoretical and philosophical foundation of Bakhtin, Ricoeur, Muntañola and Rapoport. The objective of this work is the analysis of the readings and the social use of the text, from the interviews with a varied representation of the people who make up the city of Avilés. As a synthesis of the results, the refiguration of the work and the readings establish the acceptance by citizens and representatives of a new cultural landscape - still with its unfinished ambience - capable of updating the context of the city in terms of modernity versus tradition, establishing the beginning of the regeneration of the estuary for recreational activities and a new opportunity for the entire region.